How Has the Nationwide Public Health Emergency of the COVID-19 Pandemic Affected Older Chinese Adults' Health Literacy, Health Behaviors and Practices, and Social Connectedness? Qualitative Evidence From Urban China - Chai, Xiangnan (Frontiers in Public Health, 2022)
Older Chinese adults’ daily lives have been affected significantly during the outbreak phase of the COVID-19 pandemic since January 2020. They were confronted with activity restrictions due to strict pandemic prevention. The older population also had to get accustomed to widely-used modern technologies in community management, such as health codes and WeChat groups. By late 2021, mainland China had reduced the prevalence of COVID-19, and people’s daily lives had primarily returned to pre-pandemic normality. Under China’s systematic health management during the pandemic, older Chinese adults’ responses to this nationwide public health emergency may have influenced their health in the long run. However, it remains unclear what specific health changes or improvements have occurred. Such a void in the literature is worrying, given that older adults are at high health risks due to the pandemic which, might still be with humankind for a while. Thus, it is of necessity to explore and report their health changes after this official, large-scale health intervention. In this study, 17 adults aged 55 and above were recruited as interviewees. All interviewees reside in a community located in Q district, N city of the People’s Republic of China. According to the findings, many interviewees now have better literacy in health risk prevention. Information Communicative Technologies (ICTs) play a significant role in getting access to health information. Specifically, television, WeChat chatting groups, and TikTok could be valuable information sources for older adults. As for the understanding and evaluation of health information, although older participants can distinguish COVID-19 rumors, they may sometimes feel confused about the underlying scientific logics. Regarding changes in health behaviors and practices, many older adults can integrate health information and knowledge into their daily lives. Additionally, although interviewees can keep important social connections, not all of them are familiar with using new ICTs, such as online chatting group, for social participation and engagement. The empirical evidence suggests that both the communities and the local governments can offer specific training programs to older residents for the sake of enhancing their health literacy, health behaviors and practices, and social connectedness during and after the pandemic.